Dynamics of abdominal symptoms during the start of a new therapy with elexacaftor/tezacaftor/ivacaftor using the novel CFAbd-day2day questionnaire - Mainz, Jochen G.; Barucha, Anton; Huang, Pu; Bechinger, Lilith; Duckstein, Franziska; Polte, Louise; Sadrieh, Pauline; Nährlich, Lutz; Eickmeier, Olaf; Van Dullemen, Suzanne; Eschenhagen, Patience; Schwarz, Carsten; et al. (Frontiers in Pharmacology, 2023)
Background: Elexacaftor-tezacaftor-ivacaftor (ETI) is a novel highly effective CFTR modulator combination proven to improve lung function and body weight in people with Cystic Fibrosis (pwCF) carrying a F508del mutation. Recently, we revealed significant reductions of abdominal symptoms (AS) in German, British and Irish pwCF after 24-26 weeks of ETI using the CFAbd-Score, the first PROM specifically developed and validated for pwCF following FDA guidelines.Notably, many pwCF reported marked changes in their AS during the first days of the new treatment.To capture these immediate effects, we developed the CFAbd-day2day, a CF-specific GI-diary, following FDA and COSMIN guidelines.Aims: To prospectively capture immediate dynamics of AS using the CFAbd-day2day 14 days before and 14-28 days after ETI initiation. In addition, we aim here to provide validation steps of the novel PROM concerning sensitivity to changes.To develop the CFAbd-day2day, focus groups (community voice=pwCF and their proxies and CF specialists from different fields) were repeatedly consulted. Before and under the new ETI therapy pwCF prospectively scored AS on a daily basis with the CFAbd-day2day.Results: Altogether, n=45 pwCF attended in 5 CF centers prospectively completed the CFAbd-day2day before (mean±sd: -14±7 days) and after (mean±sd: 28±23 days) ETI initiation. Whereas cumulative scores significantly decreased during the 3-4-week time frame after ETI initiation, compared to the two weeks prior to therapy, many patients who revealed a relatively stable level of AS before ETI reported changes during the first days of treatment with the highly effective CFTR modulators.Items like pain and flatulence increased in up to 21% of patients during the first 14 days of therapy but they improved during days 15-27.The CFAbd-day2day, specifically developed and in process of validation to prospectively capture GI symptoms in pwCF, provides new substantial insights into the dynamics of AS in pwCF receiving a new treatment with ETI. The novel tool is also helpful to prospectively monitor patients with specific GI problems. International implementation and further validation steps of the diary are ongoing.